The Sticky Standard of Care - Oberman, Michelle (The Hastings Center report, 2017)
The problem at the heart of “Stemming the Standard-of-Care Sprawl: Clinician Self-Interest and the Case of Electronic Fetal Monitoring,” an article by Kayte Spector-Bagdady and colleagues in the November-December 2017 issue of the Hastings Center Report, is the persistence of a suboptimal standard of care long after evidence-driven approaches would dictate a change. That problem is not simply defensive medicine, or what the authors call “standard-of-care sprawl.” Instead, it is that, in some cases, the standard of care lags behind best practices. It gets stuck. The authors point to the genesis of the stickiness problem in their passing reference to a core truth: “The problem is that standard of care is not synonymous with best or evidence-based medicine.” In my view, we might best understand the persistence of ineffective and even harmful medical interventions by acknowledging the regulatory vacuum in which such practices thrive. It is by default, not by design, that the profession relies on medical malpractice law to set the boundaries on acceptable practice.